PEMBATALAN PERJANJIAN BAKU YANG MELANGGAR UNDANG-UNDANG STUDI KASUS PUTUSAN MAHKAMAH AGUNG Nomor 368 K/Pdt.Sus-BPSK/2013 - IMMANUEL SIHITE (PREMISE LAW JURNAL, 2016)
Standard contract is a binding agreement of the stakeholders who sign it. Any loss which occurs later will be their responsibility, based on the clause of the contract, unless the clause is forbidden according to Article 18 of Law No 8/1999 on Consumer Protection. The analysis of the research is the Supreme Court’s Ruling No. 368/Pdt.Sus-BPSK/2013 in examining a special civil case on complaint about the Decision of Consumer Dispute Settlement Body in the cassation appeal between PT Express Limon Nusantara as business person and Dedek Cahyo as consumer. The research used theory of legal certainty with judicial normative and descriptive analytic methods. The ruling should have the sense of justice for those who should get legal protection so that legal certainty and justice in handing down a ruling so that there will balance in the ruling. A judge has to be fair in his ruling and give sanction upon consumers who have breached a contract. Keywords: Standard Contract, Business Person, Consumer